2014
DOI: 10.4049/jimmunol.1400498
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells: New Keys for Further Unlocking the Enigma of Fetal Tolerance and Pregnancy Complications

Abstract: The immunological alterations required for successful pregnancy in eutherian placental mammals have remained a scientific enigma since the discovery of MHC haplotype diversity and unique immune signatures among individuals. Within the past 10 years, accumulating data suggest immune suppressive regulatory T cells (Tregs) confer essential protective benefits in sustaining tolerance to the semi-allogeneic fetus during pregnancy – along with their more established roles in maintaining tolerance to self and “extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 96 publications
1
83
1
Order By: Relevance
“…How this is accomplished is one of the major enigmas of mammalian reproduction. Contrary to the long-standing hypothesis that the pregnant mother is immunocompromised (3), recent evidence suggests that the maternal immune system is intricately regulated during pregnancy, and the placenta is well guarded against infection (4)(5)(6). A few predominantly intracellular microbes are able to infect the placenta and cause pregnancy complications such as preterm labor, fetal damage, and death (5,7).…”
mentioning
confidence: 86%
“…How this is accomplished is one of the major enigmas of mammalian reproduction. Contrary to the long-standing hypothesis that the pregnant mother is immunocompromised (3), recent evidence suggests that the maternal immune system is intricately regulated during pregnancy, and the placenta is well guarded against infection (4)(5)(6). A few predominantly intracellular microbes are able to infect the placenta and cause pregnancy complications such as preterm labor, fetal damage, and death (5,7).…”
mentioning
confidence: 86%
“…Similar to prenatal L. monocytogenes infection, partial transient ablation of maternal Tregs to levels before pregnancy primes expansion and IFN-γ production among fetal-specific maternal effector T cells (25,26,53) -illustrating the sustained systemic expansion of this immune-suppressive T cell subset is essential for maintaining fetal tolerance. Fetal wastage triggered by partial depletion of maternal FOXP3 + cells in mice directly parallels blunted expansion of maternal Tregs in the peripheral blood and decidua in human pregnancy complications associated with disruptions in fetal tolerance (e.g., preeclampsia, spontaneous abortion) (19)(20)(21)(22)(23)(24), whereas overriding local immunesuppressive pathways in place to sustain fetal tolerance likely play decisive roles in the pathogenesis of fetal injury, considering the absence of fetal wastage after infection with influenza A that does not directly invade the maternal-fetal interface. Accordingly, this newfound pathway, whereby decidual chemokine expression silencing becomes functionally circumvented, may drive the underlying pathogenesis of fetal wastage after infectious as well as idiopathic disruptions in fetal tolerance, possibly representing subclinical or undiagnosed local infection (2-4).…”
Section: Monocytogenes and Influenza A Infectionsmentioning
confidence: 99%
“…Instead, overriding suppression by expanded maternal FOXP3 + regulatory CD4 + T cells (Tregs) by attenuated L. monocytogenes that do not cross the placental-fetal barrier triggers sterile fetal wastage, along with expansion and IFN-γ production by maternal T cells with fetal specificity (16)(17)(18). Direct associations between blunted expansion of maternal Tregs or their dampened suppressive properties are also recognized increasingly in many idiopathic pregnancy complications linked with disruptions in fetal tolerance (e.g., preeclampsia, spontaneous abortion, prematurity) (19)(20)(21)(22)(23)(24). This necessity for expanded maternal Tregs modeled in animal pregnancy shows that even partial transient depletion of FOXP3 + cells to levels before pregnancy unleashes expansion and activation of IFN-γ-producing maternal CD8 + effector T (Tc1) and CD4 + helper T (Th1) cells with fetal specificity that share striking commonality with disruptions in fetal tolerance instigated by prenatal L. monocytogenes infection (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have also addressed the frequency of circulating Treg cells and initial findings showed that human pregnancy was associated with increased circulating Treg cell numbers (Heikkinen et al, 2004;Sasaki et al, 2004;Somerset et al, 2004). However, the observed increase was likely due to an increase in activated non-suppressive CD4 + CD25 high T cells that were included when using the traditional gating strategies for Treg cells (Mjosberg et al, 2009;Ernerudh et al, 2011;Jiang et al, 2014). Most recent reports, using a more strict definition of Treg cells (for instance CD4 dim CD25 high or including Foxp3 and CD127) show that circulating Treg cell numbers are unaltered or even decreased (Tilburgs et al, 2008;Mjosberg et al, 2009) and this has been proposed to be due to specific Treg cell migration to the decidua (Tilburgs et al, 2008).…”
Section: Th and Treg Cellsmentioning
confidence: 99%
“…Dysregulation of Th cell populations, in particular the activation of Th1 and Th17 cells, as well as defective induction of Treg cells have been implicated in the development of pregnancy complications associated with failure to induce or maintain fetal tolerance (Saito et al, 2010;Ernerudh et al, 2011;Jiang et al, 2014).…”
Section: Treg Cellsmentioning
confidence: 99%